L'assaig com a gènere: un territori de frontera. - LIERN, VICENT SALVADOR (Scripta)
The discursive genre called essay was founded by Michel de Montaigne as a form of internal deliberation of the author and has subsequently been cultivated by important authors of Western literature. Its definition is not easy to establish. On the one hand, it has often been situated at the frontier of literary discourse, to which it is fully entitled insofar as its style exhibits a very elaborate stylistic texture and is not reduced to an expository writing typical of academic discourse. The areas of transition with literature of the self and with journalism are undoubtedly worthy of attention. On the other hand, in the field of literature it is very instructive to study its relations with various literary genres and mainly with poetry, with which it coincides because both share a strong subjectivity, but there is an important difference between the two: the essay has a more rationalist component and is not compatible with certain forms of expression of intimacy.